Hidradenitis suppurativa and squamous cell carcinoma: a systemic review of the literature - Gierek, Marcin; Niemiec, Paweł; Szyluk, Karol; Ochala-Gierek, Gabriela; Bergler-Czop, Beata (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2023)
Hidradenitis suppurativa (HS) is a chronic disease which is often recurrent and occurs as abscesses of the apocrine gland. The most common locations of HS are gluteal/perianal, axillary or inguinal. It is reasonable to assume that squamous cell carcinoma may arise from HS. As researchers in the field of dermatology, HS surgery and conventional surgical oncology, we studied whether there is any correlation between HS and neoplasms. Evidence shows a correlation between HS and squamous cell carcinoma. The aim of the study was to find literature about HS and SCC and analyse potential risk factors. This is a systemic review concerning squamous cell carcinoma and hidradenitis suppurativa.